PERAN PSIKOLOGI PENDIDIKAN DALAM TRANSFORMASI PEMBELAJARAN DIGITAL DAN SOSIAL-EMOSIONAL MAHASISWA (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study examines the role of educational psychology in guiding the transformation of digital learning and strengthening the social-emotional aspects of university students in a pesantren-based higher education context. The problem underlying this study arises from changes in students’ learning patterns caused by digital learning practices that have not been fully accompanied by adequate psychological support, resulting in decreased learning motivation, limited self-management skills, and reduced quality of social interaction. Based on this issue, the study addresses the question of how educational psychology contributes to helping students adapt academically and socially-emotionally amid the transformation of digital learning. This research employed a qualitative approach with a case study design, conducted among students in the Zaid bin Tsabit Area of Nurul Jadid Islamic Boarding School. Data were collected from the Head of the Area, counselors, and students through observation, in-depth interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings indicate that the integration of educational psychology principles plays a significant role in enhancing students’ learning independence, consistency of learning motivation, emotional management abilities, and the quality of social interaction in digital learning environments. Students who received psychological guidance demonstrated better learning adaptation compared to those who did not. This study concludes that educational psychology serves as a strategic foundation in ensuring that digital learning transformation is not solely oriented toward technological utilization, but also supports students’ psychological well-being and sustainable character development.